2014
DOI: 10.3389/fninf.2014.00005
|View full text |Cite
|
Sign up to set email alerts
|

Brain-wide map of efferent projections from rat barrel cortex

Abstract: The somatotopically organized whisker barrel field of the rat primary somatosensory (S1) cortex is a commonly used model system for anatomical and physiological investigations of sensory processing. The neural connections of the barrel cortex have been extensively mapped. But most investigations have focused on connections to limited regions of the brain, and overviews in the literature of the connections across the brain thus build on a range of material from different laboratories, presented in numerous publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 96 publications
(171 reference statements)
5
77
1
Order By: Relevance
“…Recently, other researchers working on elucidating the cortical connectome have accumulated data suggesting more profuse efferent projections from the rat (Zakiewicz et al 2014) and mouse (Zingg et al 2014; Oh et al 2014) barrel cortex than were reported in early studies, although the coronal section plane and comprehensive mapping strategies preferred in these reports likely obscure the radiating nature of the mesoscopic projection (Johnson and Frostig 2015). Indeed, the data mining in the analysis of the connectome typically imposes preconceived notions of cortical parcellation that would divide some of the continuous patterns of connectivity we have described into discrete regions before quantitative comparisons are performed (Bota et al 2012; Zingg et al 2014; Oh et al 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, other researchers working on elucidating the cortical connectome have accumulated data suggesting more profuse efferent projections from the rat (Zakiewicz et al 2014) and mouse (Zingg et al 2014; Oh et al 2014) barrel cortex than were reported in early studies, although the coronal section plane and comprehensive mapping strategies preferred in these reports likely obscure the radiating nature of the mesoscopic projection (Johnson and Frostig 2015). Indeed, the data mining in the analysis of the connectome typically imposes preconceived notions of cortical parcellation that would divide some of the continuous patterns of connectivity we have described into discrete regions before quantitative comparisons are performed (Bota et al 2012; Zingg et al 2014; Oh et al 2014).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, thalamic bursting activity can increase due to enhancement of sensory feedback gain from cortical to thalamic regions (50). Hence, the enhanced SC activation observed here could result from burst information relayed to sensory cortices from VPM and facilitated through direct cortico-tectal projections from V1 and/or S1 (24,60). Neural plasticity mechanisms are also likely recruited.…”
Section: Discussionmentioning
confidence: 99%
“…Given the reciprocal cortico-cortical connections between RFA and the two somatosensory areas, these results were unexpected [53].Other cortical (and subcortical) structures undoubtedly play a role in these distant effects of repetitive microstimulation (cf. Fig.…”
Section: Discussionmentioning
confidence: 99%